2022
DOI: 10.1080/15384047.2022.2058862
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin activates NLRC4, AIM2, and IFI16 inflammasomes and induces pyroptosis by up-regulated ISG3 transcript factor in acute myeloid leukemia cell lines

Abstract: Curcumin, the primary bioactive component isolated from turmeric, has been found to possess a variety of biological functions, including anti-leukemia activity. However, the effect of curcumin in different leukemia cells vary. In this study, we demonstrated that curcumin induced the expression of AIM2, IFI16, and NLRC4 inflammasomes in leukemia cells U937 by increasing the expression levels of ISG3 transcription factor complex, which activated caspase 1, promoted cleavage of GSDMD, and induced pyroptosis. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Then, stimulation of caspase 1 occurs to enhance cleavage of GSDMD and mediate pyroptosis. 68 The regulation of pyroptosis by curcumin has been only mentioned, while there are other types of cell death pathways especially ferroptosis and necroptosis that their modulation by curcumin in leukemia therapy should be mentioned.…”
Section: Curcumin and Leukemiamentioning
confidence: 99%
“…Then, stimulation of caspase 1 occurs to enhance cleavage of GSDMD and mediate pyroptosis. 68 The regulation of pyroptosis by curcumin has been only mentioned, while there are other types of cell death pathways especially ferroptosis and necroptosis that their modulation by curcumin in leukemia therapy should be mentioned.…”
Section: Curcumin and Leukemiamentioning
confidence: 99%
“…Zhou et al reported that GSDMD can serve as a biomarker to estimate the sensitivity of curcumin in leukaemia treatment. Therefore, pyroptosis could be a potential novel manner for treating leukaemia [ 90 ].…”
Section: Association Between Pyroptosis and Cancermentioning
confidence: 99%
“…BRAF and MEK inhibitors inhibit melanoma cancer progression via inducing pyroptosis 3. pyroptosis can release HMGB1 and enhance the progression of melanoma Acute myeloid leukaemia 1. GSDMD are upregulated and represses leukaemia progression [ 90 ] Ovarian cancer 1. GSDME is downregulated whereas GSDMD and GSDMC are upregulated and repress ovarian cancer progression [ 91 93 ] 2. lncRNA GAS5 and lncRNA HOTTIP represses ovarian cancer progression via inducing pyroptosis Oral squamous cancer 1.…”
Section: Association Between Pyroptosis and Cancermentioning
confidence: 99%
“…Curcumin has a broad variety of pharmacological effects, including anti-inflammatory, antioxidant, anti-tumor, enhancing radiotherapy and chemotherapy sensitivity, and protecting liver and kidney functions ( Hewlings and Kalman, 2017 ). It has been broadly investigated in cancers, including acute myeloid leukemia ( Zhou et al, 2022b ), prostate cancer ( Al-Rabia et al, 2022 ), breast cancer, lung cancer etc ( Giordano and Tommonaro, 2019 ).…”
Section: Natural Products Undergoing Clinical Evaluation In Pancreati...mentioning
confidence: 99%